The KCNJ11-E23K gene variant hastens diabetes progression by impairing glucose-induced insulin secretion - Sachse, G; Haythorne, E; Hill, T; Proks, P; Joynson, R; Terrón-Expósito, R; Bentley, L; Tucker, SJ; Cox, RD; Ashcroft, FM (American Diabetes Association, 2021)
The ATP-sensitive K+ (KATP) channel controls blood glucose levels by coupling glucose metabolism to insulin secretion in pancreatic β-cells. E23K, a common polymorphism in the pore-forming KATP channel subunit (KCNJ11) gene, has been linked to increased risk of type 2 diabetes. Understanding the risk-allele-specific pathogenesis has the potential to improve personalized diabetes treatment, but the underlying mechanism has remained elusive. Using a genetically engineered mouse model, we now show that the K23 variant impairs glucose-induced insulin secretion and increases diabetes risk when combined with a high-fat diet (HFD) and obesity. KATP-channels in β-cells with two K23 risk alleles (KK) showed decreased ATP inhibition, and the threshold for glucose-stimulated insulin secretion from KK islets was increased. Consequently, the insulin response to glucose and glycemic control was impaired in KK mice fed a standard diet. On an HFD, the effects of the KK genotype were exacerbated, accelerating diet-induced diabetes progression and causing β-cell failure. We conclude that the K23 variant increases diabetes risk by impairing insulin secretion at threshold glucose levels, thus accelerating loss of β-cell function in the early stages of diabetes progression.